Marine auxiliary machinery - McGeorge, H. D. (H. David) (Oxford : Butterworth/Heinemann, 1995)
The seventh edition of this classic marine textbook is now available for the first time in paperback. This highly respected book instructs both students and sea-going engineers in the operation, care and maintenance of the auxiliary machinery and apparatus on board ship and is essential reading for marine engineers preparing for British Certificates of Competency examinations, US Licenses and similar qualifications elsewhere. Designed for ease of use, the detailed treatment and practical orientation of the subject matter is presented in a very accessible manner. The inclusion of suggestions for further reading at the end of each chapter is of particular use to students and all those interested in any related titles. Alongside this, there is also sufficient theoretical background to enable the reader to fully understand the principles involved. These various features allow the book to also serve as a useful reference work for engineers in the shipbuilding and equipment manufacturing industries, as well as all sea-going engineers.
Preface; Main propulsion services and heat exchangers; Machinery service systems and equipment; Ship service systems; Valves and pipelines; Pumps and pumping; Tanker and gas carrier cargo pumps and systems; Auxiliary power; The propeller shaft; Steering gears; Bow thrusters, stabilizers and stabilizing systems; Refrigeration; Heating, ventilation and air conditioning; Deck machinery and cargo equipment; Fire protection; Safety and safety equipment; Control and instrumentation; Index.
Includes bibliographical references and index.
Keywords: Marine engines; Marine machinery; Electronic books